Biodegradative and antimicrobial activities of pseudomonas isolated from soil and water samples in Ado-Ekiti metropolis, Nigeria (Journal of Bio-Science, 2016)
Context: The release of petroleum hydrocarbon and pesticides into the environment is a major concern because of their toxigenic and carcinogenic potentials. Microorganisms which are biodegradable and most often less toxic have been found to use these materials as carbon sources. Also, the development of resistance of microbial pathogens to commercial antibiotics has necessitated an alternative to commercial antibiotics.Objectives: This study investigated the ability of Pseudomonas species isolated from soil and water samples to degrade some petroleum products and pesticides as well as its antimicrobial potency against selected pathogens.Materials and methods: Pseudomonas species were isolated from soil samples from mechanic workshop, dump sites and stream water. The isolates were tested for the ability to degrade petroleum products (diesel, engine oil and kerosene) and some pesticides. These isolates were also tested for antimicrobial activities against some pathogenic bacteria and fungi.Results: Three Pseudomonas were obtained from the samples; Pseudomonas fluorescens (DS) was isolated from a dumping site and two Pseudomonas aeruginosa, MW and SW were isolated from mechanic workshop and stream water. The three isolates showed varying ability to degrade petroleum products and pesticides. Escherichia coli, Proteus mirabillis and Serratia marcescens were susceptible to the three Pseudomonas isolates in varying degree while Staphylococus aureus and Klebsiella pneumoniae were resistant to the isolates. All the fungi except Candida albicans were susceptible to the Pseudomonas spp.J. bio-sci. 22: 09-14, 2014